O204 Simultaneous bi-hemispheric repetitive transcranial magnetic stimulation for upper limb motor recovery in chronic stroke: A double blind placebo controlled study. Issue 9 (September 2017) - Chieffo, Raffaella; Scopelliti, Giuseppe; Fichera, Mario; Di Maggio, Giovanni; Santangelo, Roberto; Guerrieri, Simone; Houdayer, Elise; Zangen, Abraham; Comi, Giancarlo; Leocani, Letizia
Abstract : Objective: repetitive transcranial magnetic stimulation (rTMS) is a promising intervention for the treatment of post-stroke motor deficits. Since the crucial role of non-primary motor cortices and contralesional brain areas is emerging for motor recovery in chronic stroke; we assessed safety and efficacy of bilateral rTMS over the motor areas associated to physical training (PT) on upper extremity (UE) motor function. Methods: double-blind, placebo-controlled trial on 20 patients with chronic stroke conditioning moderate to mild upper limb motor impairment. Eleven sessions of high frequency rTMS were delivered with the H-coil over the motor areas bilaterally. Subjects were randomly allocated to the real rTMS plus PT or the placebo (sham) rTMS plus PT. UE impairment was evaluated by the Fugl-Meyer assessment for UE (FM-UE), Modified Ashworth Scale (MAS) and hand grip strength at baseline (T0), after treatment (T1) and one-month follow-up (T2). Results: no serious adverse events were reported. At T1 FM-UE significantly improved in both groups, while at T2 the improvement was significant only for the real group. The improvement was significantly higher in the real compared with the sham group. In the real group, greater improvement in FM-UE was found in patients moderately  impaired compared with less impaired at baseline. Spasticity and hand grip strength also significantly improved in the real group at T1 and amelioration of spasticity persisted also at T2. Conclusion: bilateral high-frequency rTMS with H-coil associated with PT is safe and enhances the effect of PT alone. Although plegic patients were not included, subjects with moderate rather than mild motor impairment may mainly benefit from this stimulation protocol.